2022
DOI: 10.1021/acsanm.2c02982
|View full text |Cite
|
Sign up to set email alerts
|

Amorphization of LaCoO3 Perovskite Nanostructures for Efficient Oxygen Evolution

Abstract: It has become a challenge to further enhance the electrocatalytic performance of perovskite oxides due to their limited active surface area. Herein, we propose a top-down strategy for the amorphization of crystalline LaCoO3 nanopowders with significantly enhanced specific surface area and electrocatalytic oxygen evolution reaction (OER) activity and durability, in which the overpotential at the current density of 10 mA cm–2 reduced from 405 to 293 mV, and the Tafel slope decreased from 96.6 to 63.4 mV dec–1. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…There is also a satellite peak at 717.9 eV . From Table , we can see that with Fe doping, the ratio of M 2+ /M 3+ increases, enriching oxygen vacancies (OVs) and suppressing direct electron–hole recombination . In short, the XPS results further demonstrate that LaCo 0.9 Fe 0.1 O 3 /g-C 3 N 4 composites were successfully obtained and that the main electron transfer pathway was from LaCo 0.9 Fe 0.1 O 3 to g-C 3 N 4 .…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…There is also a satellite peak at 717.9 eV . From Table , we can see that with Fe doping, the ratio of M 2+ /M 3+ increases, enriching oxygen vacancies (OVs) and suppressing direct electron–hole recombination . In short, the XPS results further demonstrate that LaCo 0.9 Fe 0.1 O 3 /g-C 3 N 4 composites were successfully obtained and that the main electron transfer pathway was from LaCo 0.9 Fe 0.1 O 3 to g-C 3 N 4 .…”
Section: Resultsmentioning
confidence: 79%
“…Through a large number of tests, we can prove that Fe is successfully doped and increases the oxygen vacancy. Our study found that the band gap of LaCo x Fe 1– x O 3 after Fe doping is smaller, the specific surface area is reduced, and the ratio of M 2+ /M 3+ is increased by X-ray photoelectron spectroscopy (XPS) testing, with the introduction of oxygen defects . This reduces the direct recombination of electron–hole pairs and effectively suppresses photogenerated electron–hole pair recombination .…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…It is associated with the amorphization of the LSCO-900 surface and the appearance of chemical defects due to a positive core-level shift of 0.4−1.2 eV. 35 Figure 10c shows Sr 3d spectra, which exhibit two main components from the perovskite lattice-bound Sr lat at binding energies of 131.6 eV (Sr 3d 5/2 ) and 133.4 eV (Sr 3d 3/2 ) for LSCO-900 before electrocatalysis. In addition, a shoulder with higher binding energies of 135.2 eV from surface Sr surf is also presented, which is usually associated with surface strontiumrich phases often observed for LSCO materials.…”
Section: Electrocatalytic Propertiesmentioning
confidence: 99%
“…However, the high electrocatalytic activity of perovskites for OER in an alkaline medium is primarily the result of the redox behavior of the hybridization of transition metal 3d and oxygen 2p orbits . Numerical studies of perovskites as electrocatalysts revealed that, in addition to the chemical composition, activity in oxygen electrocatalysis reactions is also affected by a significant number of factors, namely, method and conditions of preparation of the material (annealing at different temperatures and in a controlled atmosphere can cause different types of defects on the surface); , particle size, porosity, and shape (affects active surface area); , doping; ,,,, and amorphization of the surface …”
Section: Introductionmentioning
confidence: 99%